2019
DOI: 10.1177/0748233719825720
|View full text |Cite
|
Sign up to set email alerts
|

The effect of manganese exposure on GnRH secretion via Nrf2/mGluR5/COX-2/PGE2/signaling pathway

Abstract: There are limited studies focused on the precise mechanism of gonadotropin-releasing hormone (GnRH) secretion dysfunction after overexposure to manganese (Mn). The objective of the present study was to explore the mechanism of Mn disruption of GnRH synthesis via nuclear factor erythroid-2-related factor-2 (Nrf2)/metabotropic glutamate receptor-5 (mGluR5)/cyclooxygenase-2 (COX-2)/prostaglandin E2 (PGE 2) signaling pathway in vitro and in vivo. Primary astrocytes were cultured and treated with different doses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Similarly, it has been demonstrated that MnCl 2 concentrations of 12.5, 25, and 50 mg/kg can induce differences in the expression of Nrf2-related proteins, resulting in increased ROS levels in the glial cells of mice. Consequently, low Mn concentrations activated the Nrf2 pathway and increased HO-1 and NQO1 expression, whereas high Mn concentrations inhibited these changes (Qi et al, 2019). Although Mn is an essential trace nutrient for organisms because of its role in the function as an enzymatic cofactor and ROS scavenger, these effects are confined to low concentrations and appropriate exposure times (Zeinert et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been demonstrated that MnCl 2 concentrations of 12.5, 25, and 50 mg/kg can induce differences in the expression of Nrf2-related proteins, resulting in increased ROS levels in the glial cells of mice. Consequently, low Mn concentrations activated the Nrf2 pathway and increased HO-1 and NQO1 expression, whereas high Mn concentrations inhibited these changes (Qi et al, 2019). Although Mn is an essential trace nutrient for organisms because of its role in the function as an enzymatic cofactor and ROS scavenger, these effects are confined to low concentrations and appropriate exposure times (Zeinert et al, 2018).…”
Section: Discussionmentioning
confidence: 99%